Team internal social capital and entrepreneurial learning: a dual-path exploration in new venture teams - Tingting Song; Liuqi Sun; Jiaxin Wang; Chengyan Li (Humanities & Social Sciences Communications)
Abstract The mechanisms of team internal social capital and entrepreneurial learning relationships in new venture teams (NVT) are relatively under-studied. This study investigates the association between internal social capital and entrepreneurial learning and the mediating roles of shared mental models and organisation-based self-esteem. Study 1 collected data from 284 participants from 111 NVTs in Eastern China. The hypotheses were tested using a multilevel structural equation modelling technique. The findings showed that (1) team internal social capital positively influenced entrepreneurial learning, and (2) shared mental models and organisation-based self-esteem both mediated this relationship, unveiling a dual-process mechanism. In Study 2, we conducted semi-structured interviews with a convenience sample of 14 participants from 6 NVTs in Eastern China. The results showed that internal social capital shared mental models, and organisation-based self-esteem influenced entrepreneurial learning in NVTs. This study is one of the first to use qualitative and quantitative analyses to investigate the mechanisms underlying the relationship between team internal social capital and entrepreneurial learning. The results suggest that team internal social capital promotes positive entrepreneurial behaviour, highlighting the importance of team internal social capital and entrepreneurial learning in organisational development. It can also provide indicators for those wanting to support new ventures.